Training and Guidance in Use Software Wingeom 2D and 3D in Learning Geometry to Improve the Professionalism of Junior High School Teachers In Tanggetada District, Kolaka District, Southeast Sulawesi Province - Supu, Supratman; Herlina (CV. AFDIFAL MAJU BERKAH, 2023)
This service aims to increase the professionalism of junior high school teachers in learning geometry by using Mathematics Learning Media, namely the use Sofware Wingeom 2D and 3D. This was done because looking at the problems that are generally faced by teachers in research, namely the lack of utilization and knowledge of teachers in the use of Wingeom-Based Mathematics Learning Media, in schools teachers are known that one of their weaknesses is the lack of work in the field of scientific work and research caused by erroneous one of them is the inadequacy of teachers in using mathematics learning media which can make it easier for them to be able to work. Program Wingeom 2D and 3D is a computer application program designed to support geometry learning, both two-dimensional and three-dimensional. This program can be used asmind tools in learning geometry, where teachers can use it to develop a dimensional geometric framework. With programs Wingeom It is hoped that later the teacher will be able to explore, observe, do shape animation and display dimensional geometry material, in addition to the program Wingeom 2D and 3D are expected to help visualize a geometric concept clearly so that teachers will more easily understand geometric concepts so that it will have an impact on improving the quality of teachers in the learning process, especially learning geometry. The mandatory outputs to be achieved are (1). One scientific article published in a journal with ISSN or proceedings from a national seminar. (2) Publication in print/online/repocitory mass media PT. (3). Increased competitiveness (increase quality, quantity, and added value of goods, services, product diversification, or other resources depending on the type of activity proposed. (4). Increasing the application of science and technology in society (mechanization, IT, and management). (5) Improvement of community values (art, culture, social, politics, security, peace, education, and health. Meanwhile, Additional Outcomes are in the form of (1). method or system; product (goods or services). (2). HKI, (3). Books with ISSN, (4). TTG Innovation, and, (5). International Publications. Method used in this training and mentoring include: (1) talk and question and answer about steps usage stepssoftware Wingeom 2D and 3D in learning geometry, (2) discussion groups directed on the steps of use software Wingeom 2D and 3D in learning geometry, (3) guidance and each simulation usage stepssoftware Wingeom 2d and 3D in learning geometry, (4) practice direct use of each step usage software Wingeom 2D and 3D dalam learning geometry, (5) giving related assignments usage software Wingeom 2D and 3D dalam geometry learning.